The duty of analytical reasoning in Civil Procedure and the bridges with the theory of legal argumentation (Research, Society and Development, 2022)
The present work is guided by the need to investigate the importance of theories of legal argumentation for the application of the duty of analytical reasoning formed by the governing norms of the Code of Civil Procedure, dogmatized by the concern to guarantee rationality to judicial decisions. Thus, starting from studies and bibliographical research, it finds the construction of a discussion that encompasses the concept of sentence in our contemporary paradigm of guardianship of rights, in the Democratic State, delimiting the legitimizing role of the Judiciary. Still, it addresses the formation of a duty of analytical reasoning, based on the duty of collaboration, as a meta-criterion of validity of the reasons justifying the court decision. In the end, it concludes for the importance of theories of argumentation, stating that the identification of the context of justification, outlined by its scholars, has contributed to dogmatics, meeting the concerns of rationality in arguments and, as a result, criteria of control and legal certainty.